Rapid portlet development with WebSphere portlet factory : step-by-step guide for building your own portlets - Bowley, David (IBM Press, Pearson, 2009)
The Step-by-Step Guide to Building World-Class Portlet Solutions-Fast! Portlet development traditionally has been difficult and time-consuming, requiring costly resources and specialized expertise in multiple technologies. IBM ® WebSphere ® Portlet Factory simplifies and accelerates portlet development, enabling developers to build world-class portlet solutions without in-depth knowledge of portal technology. Expert developer David Bowley walks you through several of today's most common portlet development scenarios, demonstrating how to create powerful, robust portlets quickly and cost-effectively. Each walkthrough contains all the step-by-step instructions, detailed guidance, fast answers, and working sample code you need to get tangible results immediately . The best resource available on WebSphere Portlet Factory, this bookreflects Bowley's unsurpassed experience constructing large enterprise portals. Bowley covers everything from back-end integration to user interface and AJAX techniques, helping you choose the right builder tool for each task, and define high-level instructions that generate superior code artifacts. His example projects are simple enough to understand easily, but sophisticated enough to be valuable in real-world development. This book will be indispensable to every developer who wants to succeed with WebSphere Portlet Factory, including Java"! J2EE"! and SOA developers at all levels of expertise, as well as Lotus ® Notes ® developers transitioning to WebSphere Portal. Coverage includes · Creating robust portlets: tips, tricks, shortcuts, and previously undocumented 'gotchas' · Incorporating Web services, Domino ® views/forms, and SQL data sources into your portlets · Formatting information for more effective display · Adding UI controls, charts, validation, Java methods, and other capabilities · Displaying context-sensitive content · Using AJAX in your portlets · Communicating between portlets · Implementing error handling, logging, and security